2022
DOI: 10.3389/fnut.2022.1025396
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of 25-hydroxyvitamin D levels and non-alcoholic fatty liver disease in obese children: A possible strategy to promote early screening of NAFLD

Abstract: F and Tsopmo A ( ) Relationships of -hydroxyvitamin D levels and non-alcoholic fatty liver disease in obese children: A possible strategy to promote early screening of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…There are large differences in the prevalence of NAFLD in children, as reported by recent studies compared to those of 5-10 years ago [7,9], and this primarily indicates a permanent increase over the years. These discrepancies may be due to the heterogeneity of the criteria used, as well as the mixed groups of children and adolescents [14].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…There are large differences in the prevalence of NAFLD in children, as reported by recent studies compared to those of 5-10 years ago [7,9], and this primarily indicates a permanent increase over the years. These discrepancies may be due to the heterogeneity of the criteria used, as well as the mixed groups of children and adolescents [14].…”
Section: Discussionmentioning
confidence: 84%
“…On the contrary, other studies have not identified relationships between vitamin D insufficiency/deficiency and the histopathological aspects of NAFLD, nor with most components of MS, obesity or BMI [21]. Some authors consider that vitamin D has an anti-inflammatory rather than an anti-obesity effect [62], and others consider that the deficit is an independent factor for NAFLD [9]. In addition, in the first meta-analysis that investigated the link between vitamin D deficiency and NAFLD in children, the authors found an association that was not preserved when analyzing subgroups based on age, region and BMI [61], while other authors failed to demonstrate a direct relation of vitamin D with NAFLD [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations